1998
DOI: 10.1002/(sici)1097-0215(19981209)78:6<707::aid-ijc7>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and other beverage use and prostate cancer risk among Canadian men

Abstract: There are very few large scale studies that have examined the association of prostate cancer with alcohol and other beverages. This relationship was examined in a case‐control study conducted in 3 geographical areas of Canada [Metropolitan Toronto (Ontario), Montreal (Quebec), and Vancouver (British Columbia)] with 617 incident cases and 637 population controls. Complete history of beverage intake was assessed by a personal interview with reference to a 1‐year period prior to diagnosis or interview. In age‐ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 18 publications
4
71
1
Order By: Relevance
“…A similar trend was observed for death from all types of cancer in a pool of Danish cohort studies [20], for alcoholic beverage consumption in relation to risk for colorectal cancer [21][22][23] and for the association of alcohol intake and small bowel adenocarcinoma in a European multicentre case-control study [24]. On the other hand, beer consumption (P10 g alcohol/day) was reported to significantly decrease the risk of prostate cancer (odds ratio = 0.68 adjusted for age and total energy intake; 95% confidence interval (CI) = 0.49-0.94) in comparison with non-drinking of beer in a Canadian study including 1253 subjects (617 cases and 636 controls) [25]. Also, after a 12 year follow up in a large prospective cohort study of Finish male smokers (alpha-tocopherol, beta-carotene cancer prevention study) recently a decreased relative risk (RR) for renal cell cancer was reported for both the highest alcohol intake category (>25.7 g alcohol/day, RR = 0.53; 95% CI = 0.34-0.83) and for the highest beer intake category (>7.5 g ethanol/day, RR = 0.55; 95% CI = 0.36-0.85) [26].…”
Section: Beer Consumption and Cancer Incidence: Epidemiological Evidencesupporting
confidence: 62%
“…A similar trend was observed for death from all types of cancer in a pool of Danish cohort studies [20], for alcoholic beverage consumption in relation to risk for colorectal cancer [21][22][23] and for the association of alcohol intake and small bowel adenocarcinoma in a European multicentre case-control study [24]. On the other hand, beer consumption (P10 g alcohol/day) was reported to significantly decrease the risk of prostate cancer (odds ratio = 0.68 adjusted for age and total energy intake; 95% confidence interval (CI) = 0.49-0.94) in comparison with non-drinking of beer in a Canadian study including 1253 subjects (617 cases and 636 controls) [25]. Also, after a 12 year follow up in a large prospective cohort study of Finish male smokers (alpha-tocopherol, beta-carotene cancer prevention study) recently a decreased relative risk (RR) for renal cell cancer was reported for both the highest alcohol intake category (>25.7 g alcohol/day, RR = 0.53; 95% CI = 0.34-0.83) and for the highest beer intake category (>7.5 g ethanol/day, RR = 0.55; 95% CI = 0.36-0.85) [26].…”
Section: Beer Consumption and Cancer Incidence: Epidemiological Evidencesupporting
confidence: 62%
“…68) On the other hand, several studies, like our study, have found no association between alcohol and prostate cancer. 43,[69][70][71][72][73][74] A recent experimental study showed a direct inhibitory effect of low concentrations of antioxidant wine polyphenols on the proliferation of human prostate cancer cell lines, and suggested potential beneficial effects of wine and other phenol-containing foods or drinks for the control of prostate cancer cell growth. 75) However, we could not examine this effect because too few subjects drank wine (9.7%).…”
Section: Discussionmentioning
confidence: 99%
“…5 Jain and colleagues reported on a case-control study that examined the association of beverage intake and the risk of prostate carcinoma. 6 Examining 617 patients with prostate carcinoma and 637 control participants (individuals without prostate carcinoma), those investigators found a slightly decreased risk of prostate carcinoma with tea intake (not specifically green tea) of more than 500 grams per day, as measured in fluid weight (odds ratio, 0.70; 95% confidence interval, 0.50 -0.99). Studying black tea, a more oxidized form of tea, Heilbrun et al reported a significant, inverse correlation between tea consumption and prostate carcinoma risk.…”
mentioning
confidence: 99%